2020
DOI: 10.1039/d0ra01845g
|View full text |Cite
|
Sign up to set email alerts
|

Small organic molecules with tailored structures: initiators in the transition-metal-free C–H arylation of unactivated arenes

Abstract: A small organic molecule was tailored for the efficient synthesis of biphenyl and its derivatives from aryl iodides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The radical mechanism for biaryl formation via cross-coupling of arenes with aryl halides under different conditions has been proposed in several literature studies. , In the present work, a radical mechanism is also proposed on the basis of the control experiments and the computational studies.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The radical mechanism for biaryl formation via cross-coupling of arenes with aryl halides under different conditions has been proposed in several literature studies. , In the present work, a radical mechanism is also proposed on the basis of the control experiments and the computational studies.…”
Section: Resultsmentioning
confidence: 91%
“…In the past 2 decades, under transition-metal-free conditions, efficient procedures for biaryl syntheses from cross-coupling reactions of arene and aryl halides promoted by bases have also been developed . As shown in Scheme , with the use of different ligands, the alkali salts of KO t Bu, NaO t Bu, and NaH have been found to be efficient promoters or catalysts for this transformation …”
Section: Introductionmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information. [31][32][33][34][35][36][37][38][39][40][41][42]…”
Section: Supporting Informationmentioning
confidence: 99%
“…It was reported that the t-BuOK-promoted arylation of iodo thiophenes and iodo pyridines with benzene can be catalyzed by simple organic molecules containing heteroatoms such as nitrogen and oxygen (Scheme 3). 11 Scheme 3 Tailored structure-mediated arylation of iodo heteroarenes A method was reported for the intramolecular arylation of N-(2-iodobenzyl)indoles bearing 1,10-phenanthroline, potassium tert-butoxide, and chlorobenzene (Scheme 4). 12 The method served to synthesize various 6H-isoindolo[2,1-a]-indole derivatives in high yields.…”
Section: Scheme 2 Incl3-catalyzed Arylation Of π-Deficient Heterocycles With 1hindolesmentioning
confidence: 99%
“…It was reported that the t-BuOK-promoted arylation of iodothiophenes and iodopyridines with benzene can be catalyzed by simple organic molecules containing heteroatoms such as nitrogen and oxygen (Scheme 3). 11 Using a cat-…”
Section: Scheme 2 Incl 3 -Catalyzed Arylation Of -Deficient Heterocycles With 1h-indolesmentioning
confidence: 99%